Pengaruh Penggunaan Model Pembelajaran Role Playing Terhadap Peningkatan Kemampuan Bercerita Tentang Cerita Fantasi Siswa Kelas VII SMP Negeri 2 Iborongborong Tahun - Leben Panggabean; Berliana Simanjuntak (Public Service and Governance Journal, 2023)
This research aims to find out the influence of the role playing learning model on increasing the ability to tell fantasy stories about class VII students at SMP Negeri 2 Siborongborong for the 2022/2023 academic year. The population in this study was 252 students. The sample in this study was 34 students for the experimental group and 32 students for the control group. So the sample in this study was 66 students taken using a random technique. The instruments used to collect data are treatment or practice instruments. The method used in this research is an experimental method with a posttest only design research design. Hypothesis testing is carried out using the "t" test. From data collection, the experimental group's average value was = 77.21 and the control group's average value was = 59.53. Based on the normality test, the results of the experimental group and control group were declared to be normally distributed. Then, based on the Homogeneity test it was stated that the sample came from a homogeneous population. After the normality test and homogeneity test were carried out, it was found to be 4.911. Next, this was consulted with the t table at the significance level α=0.05 with dk=(N1+N2)-2=(34+32)-2=64. From dk 64, the significance level α=0.05 = 1.669 is obtained. Thus, tcount > ttable, namely 4.911 > 1.669. Thus the alternative hypothesis (Ha) is accepted. So it can be concluded that it has a positive effect on the ability to tell fantasy stories by VII students at SMP Negeri 2 Siborongborong for the 2022/2023 academic year.